Software development for 2D force feedback device - Sati, M.; Ba Waqash, A.; Tymkovych, M. Y.; Kostin, D. O. (Харків, ХНУРЕ, 2019)
The article addresses the issue of developing software for the force-feedback device. Modern software haptic devices analyzed. The need to develop its own software for the exchange and management of this type of device, namely a 2d force feedback device, is shown. The main structural blocks of the developed software are shown. The next step is the implementation of the proposed concepts in the form of the software part of the device that is in development
Keywords: force-feedback; software